(untitled) (Italian Journal of Public Health, 2012)
The common pool of knowledge between veterinary and medical medicine has been frequently exploited to provide insights into basic biomedical science and its application in such areas as vaccine development, therapeutics and diagnostics. In this paper the essential interplay between the disciplines of medicine and veterinary medicine is discussed and illustrated in detail in such areas as prion diseases, zoonotic infectious diseases and genetic diseases of dogs.Considerations are also made about the integration of medical and veterinary education, with indications of the critical needs for maximizing the opportunities for “One Medicine" both in medical and veterinary education and for research.The essential and fascinating interplay between medicine, veterinary medicine and basic biomedical sciences can do more to advance knowledge in both medicine and veterinary medicine than either can achieve on their own....